Prema's Cultural Hybridity and Diasporic Identity in Seasons of Flight by Manjushree Thapa - Adhikary, Ramesh Prasad (Academia Research Journal, 2023)
The objective of this study is to shed light on the struggles and conflicts experienced by Nepali immigrants in the United States of America, as they encounter and attempt to appropriate western culture and lifestyle while being haunted by their native culture and tradition. The novel Seasons of Flight is a portrayal of the cultural encounters and appropriations experienced by immigrants in the United States of America. It highlights the issues of isolation, alienation, identity crisis, and accommodation that immigrants face when they try to assimilate and internalize the culture and lifestyle of the host country. The topic of identity in diasporic literature is discussed in this study, particularly in light of multiculturalism and hybrid identities. This research applies the perspective of diaspora to analyze the cultural encounters and appropriations depicted in Seasons of Flight. The research reviews the literature on diaspora theory, multiculturalism, and hybrid identity, and examines how the protagonist, Prema, undergoes trials and tribulations in her attempt to fit into the multicultural American society. The research also analyzes the conflicts between tradition and modernity portrayed in the novel, and discusses the issues of collective identity, shared belonging, religious beliefs, and commitment for unity that guide immigrants. The research finds that the cultural encounters and appropriations experienced by Nepali immigrants in the United States of America are a general plight of diasporic people. The research concludes that despite the modern amenities and aspirations offered by the multicultural American society, diasporic subjects like Prema undergo with cultural encounters and appropriations, which may lead to identity crisis and hybridity. This research highlights the importance of recognizing and respecting cultural diversity, and the need for immigrants to balance their native culture and tradition with the culture and lifestyle of the host country to overcome the challenges of cultural encounters and appropriations.